(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
“Exploring the Origin of the Universe” (Liu, 2024) discusses space and time, while “The Second Exploration of the Origin of the Universe” (Liu) delves into existence in space. This represents humanity’s endeavor to use language, words, numbers, and science to discuss these questions. Why don’t animals and stones engage in such discussions? Why do humans utilize information to discuss these pieces of information? Humans have stumbled upon information; how should they deal with it? There are no correct or standard answers; each person is a philosopher, engaging in contemplation. This article briefly discusses the existence of humanity.